Biblical and Teological fundaments of human development in the encyclical letter “Caritas in Veritate” by Benedict XVI - Gutiérrez Velasco, Flavio (2010)
Now that human development is conceived unilaterally, only the material aspect, Pope Benedict XVI has chosen to dedicate this encyclical integral human development: it is not possible in a reductive vision of man, but as a whole: economic, social, political, technological, cultural and religious-moral. Very often ignores the religious dimension and in this lies the Church’s contribution to human development: “Only in charity, illumined by the light of reason andfaith, is it possible to pursue development goals that possess a more humane and humanizing value” (CaritasinVeritate, n.9). In this paper we seek to discover the biblical and theological foundations of this encyclical letter which, in general, are in line with classical and biblical theology, and with the tradition of the Church, but in the current context of globalization.